Cost of anaesthesia. - Astley, B A (1982)
The major contributory factor to the cost of anesthesia today are the increases in medical salaries that have kept pace with inflation, commanding 68% of the total expenditure. The current position has been compared with that of 20 years ago. This outline could be used as a framework for departmental budgeting.